2012
DOI: 10.1182/blood.v120.21.3759.3759
|View full text |Cite
|
Sign up to set email alerts
|

EUTOS Score Is Also Valid in CML Patients Not Involved in Clinical Studies

Abstract: 3759 Data of 2060 patients from the in-study registry of the European Outcome and Treatment Study (EUTOS) for CML were used to develop and validate the EUTOS score [1]. All these patients were included in prospective controlled clinical trials. The EUTOS score aims to support clinical decision making within the first 18 months after initiation of treatment with imatinib. Patients who did not achieve complete cytogenetic remission (CCyR) within 18 months had a lower probability of achieving CCyR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Second, Hoffmann et al . reported that the EUTOS score was able to identify patients with a significantly higher risk of not achieving CCyR and of disease progression among 316 patients receiving imatinib who were not involved in clinical trials, thus suggesting that the utility of the EUTOS score may not be confined solely to patients enrolled in clinical trials. Third, another study by Hoffmann et al .…”
Section: Eutos Scorementioning
confidence: 99%
“…Second, Hoffmann et al . reported that the EUTOS score was able to identify patients with a significantly higher risk of not achieving CCyR and of disease progression among 316 patients receiving imatinib who were not involved in clinical trials, thus suggesting that the utility of the EUTOS score may not be confined solely to patients enrolled in clinical trials. Third, another study by Hoffmann et al .…”
Section: Eutos Scorementioning
confidence: 99%